The influence of a short-term gluten-free diet on the human gut microbiome. Issue 1 (December 2016) - Bonder, Marc; Tigchelaar, Ettje; Cai, Xianghang; Trynka, Gosia; Cenit, Maria; Hrdlickova, Barbara; Zhong, Huanzi; Vatanen, Tommi; Gevers, Dirk; Wijmenga, Cisca; Wang, Yang; Zhernakova, Alexandra
Abstract Background A gluten-free diet (GFD) is the most commonly adopted special diet worldwide. It is an effective treatment for coeliac disease and is also often followed by individuals to alleviate gastrointestinal complaints. It is known there is an important link between diet and the gut microbiome, but it is largely unknown how a switch to a GFD affects the human gut microbiome. Methods We studied changes in the gut microbiomes of 21 healthy volunteers who followed a GFD for four weeks. We collected nine stool samples from each participant: one at baseline, four during the GFD period, and four when they returned to their habitual diet (HD), making a total of 189 samples. We determined microbiome profiles using 16S rRNA sequencing and then processed the samples for taxonomic and imputed functional composition. Additionally, in all 189 samples, six gut health-related biomarkers were measured. Results Inter-individual variation in the gut microbiota remained stable during this short-term GFD intervention. A number of taxon-specific differences were seen during the GFD: the most striking shift was seen for the familyVeillonellaceae (classClostridia ), which was significantly reduced during the intervention (p  = 2.81 × 10−05 ). Seven other taxa also showed significant changes; the majority of them are known to play a role in starch metabolism. We saw stronger differences in pathway activities: 21 predicted pathway activity scores showed significant association to the change in diet. We observed strong relations between the predicted activity of pathways and biomarker measurements. Conclusions A GFD changes the gut microbiome composition and alters the activity of microbial pathways.